Directional drop transport achieved on high-temperature anisotropic wetting surfaces - Liu, Chengcheng (Advanced materials (Deerfield Beach, Fla.), 2014)
© 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.